Commodifying sustainability: Development, nature and politics in the palm oil industry. (September 2019) - Pye, Oliver
Highlights: The palm oil industry is neither sustainable nor a viable development model. Certification represents a technical fix which neglects underlying dynamics of power, class, gender and accumulation. The fetishised commodity 'certified sustainable palm oil' has no impact on the regional scale of expansion. Working conditions in the plantations and mills entrench social inequality and poverty. Alternative sustainability futures emerge from struggles over land rights, working conditions and environmental justice. Abstract: Palm Oil is a highly successful flex crop that has become a development engine in Southeast Asia and elsewhere. If the industry-led stakeholder initiative, the Roundtable on Sustainable Palm Oil (RSPO) is to be believed, there is also a mechanism in place that can guarantee sustainable production along the supply chain. But what counts as sustainable and what does this mean on the ground in producing countries like Malaysia and Indonesia? This article argues that the form of sustainability offered by certification schemes such as the RSPO fetishes the commodity palm oil in order to assuage critical consumer initiatives in the North. This technical-managerial solution is part of a larger project: the "post-political" climate politics regime (Swyngedouw) that attempts to "green" the status quo. But certification obscures the problem that it is not the commodity itself but the social relations of nature in the production of the commodity that need to become sustainable. It will be shown that despite certification, these social relations of nature are contested in Southeast Asia. Social and political struggles over land rights, workers' rights and environmental justice are repoliticising debates over palm oil, opening up trajectories of eco-social transformation that make alternative sustainability futures for palm oil possible.